The Effect of Price on the Buying Interest of Super Air Jet Airline Users at Sultan Thaha Syaifuddin Airport Jambi - Ria Ryoko; Kartika Fajar Nieamah (CV. Rayyan Dwi Bharata, 2023)
The purpose of this study was to determine the effect of price on the buying interest of Super Air Jet airline users. In addition, this research is also to find out how much influence the price has on the buying interest of Super Air Jet airline users at Sultan Thaha Syaifuddin Airport, Jambi. This research was conducted from 17 January 2023 to 17 February 2023, at Sultan Thaha Syaifuddin Airport, Jambi. The research was conducted in the passenger waiting room using secondary data and primary data. Includes data obtained from distributing questionnaires carried out in the passenger waiting room, as well as using documentation from data collection carried out for passengers. There are 2 (two) hypotheses tested in this study. The research was conducted on 100 samples of Super Air Jet passengers at Sultan Thaha Syaifuddin Airport, Jambi. Sampling method using the Slovin method. Primary data comes from questionnaires distributed to 100 Super Air Jet passengers and secondary data comes from literature reviews, archive centers and book sources. Data quality testing is carried out by testing reliability and validity. The results of the research show that all the data are quite reliable and valid to use. Primary data were analyzed using simple linear regression analysis. Basic assumption test consisting of normality and linearity tests. The t test was conducted to test the research hypothesis. The regression model used has met the requirements in testing the basic assumptions. Price has a calculated t-value of 14,903 with a significant level of 0,000 (less than 5% level) so it can be concluded that with a 95% confidence level, the effect of price on purchase intention of Super Air Jet airline users is significant. The calculated r value is 0.833 with an R2 value of 69.%. So it can be concluded that there is an influence of variable X on variable Y of 69%.